PENGARUH TAX AVOIDANCE, DEWAN DIREKSI, KOMISARIS INDEPENDEN, KEPEMILIKAN MANAJEMEN, UKURAN PERUSAHAAN, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN (Students' Journal of Accounting and Banking, 2014)
The purpose of this study was to examine the effect of tax avoidance, Board of directors, independent directors, management ownership, firm size, and institutional ownership on firm value.The population in this study were manufacturing companies listed in Indonesia Stock Exchange (IDX) from 2008 to 2012. Sampling metod based on specified criteria namely purposive sampling with data analisis using multiple linear regresion.The results showedthat: (1) Effectivetax rateanda significantnegative effecton firm value. (2) Firm sizeon firm value. (3) The board of directorshas no effecton firm value. (4) Independent commissionerhas no effecton firm value. (5) Management ownershiphas no effecton firm value. (6) Institutional ownershiphas no effecton firm value.Keywords: Tax avoidance, size company, board ofdirectors, independent directors, managementownership, institutional ownership